2021
DOI: 10.21138/gf.691
|View full text |Cite
|
Sign up to set email alerts
|

Cartografías para la acreditación del riesgo de inundaciones: SNCZI y PATRICOVA en la Comunidad Valenciana (España)

Abstract: RESUMENEn España, las administraciones públicas con competencias en materia de ordenación del territorio y planificación urbanística no disponían hasta fechas recientes de una herramienta jurídica que acreditara el riesgo de inundación en un espacio geográfico. La Ley del Suelo 2/2008 (mod. 2015), resuelve este problema, puesto que obliga a realizar mapas de riesgos naturales como documento acreditativo de riesgo. En la actualidad, existen varias cartografías oficiales sobre inundaciones en el ámbito nacional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…With respect to the official maps of Spain (SNCZI) and the Region of Valencia (PATRI-COVA), Olcina et al (2021) undertook a comparative analysis of the two flood maps, identifying a series of differences with respect to the impact on the surface and buildings [17]. Interestingly, they also indicate that the SNCZI map does not include the floods generated by minor river channels as they are not recognised as Public Water Domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the official maps of Spain (SNCZI) and the Region of Valencia (PATRI-COVA), Olcina et al (2021) undertook a comparative analysis of the two flood maps, identifying a series of differences with respect to the impact on the surface and buildings [17]. Interestingly, they also indicate that the SNCZI map does not include the floods generated by minor river channels as they are not recognised as Public Water Domain.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in the natural risk includes a series of measures from prevention to emergency management [16]. One of the most important measures to mitigate the negative effects of the floods and manage an emergency is risk mapping [17]. Mapping is one of the most efficient measures for reducing natural risk [18].…”
Section: Introductionmentioning
confidence: 99%
“…To preface our dialogue with some historical context, we trace a non-exhaustive, twofold timeline of events throughout the past 20th century: developments in meteorological research on the one hand, alongside Europe’s political and cultural formation on the other (Table 1). European climatology, we discern, once adopted an “Atlantic outlook", following weather front theories from the Norwegian Meteorological School in the early 1900s, then arguably turned towards what might be called a Mediterranean outlook", following studies of Saharan air over the Mediterranean Basin (Jansa Guariola, 1959; Olcina Cantos, 2008; Gil Olcina and Olcina Cantos, 2021: 646-652). More recently, the implementation of surveillance networks and organisations validates North African atmospheric dynamics as important processes in European meteorology (METEOSAT geostationary satellite and Doppler-type meteorological radars, EUMETSAT, ECMWF).…”
Section: Storying Weather: Towards Critical Theoriesmentioning
confidence: 95%
“…Basically, it was concluded that the canalization generated a false sense of security [28] that led to the construction of houses in flood zones. Three years later, in 2019, the last major flood occurred in this area, which showed that structural solutions are not sufficient to prevent this type of catastrophe [29]. During this episode, Almoradí and other adjoining localities were left without water supply.…”
Section: Case Studymentioning
confidence: 99%
“…Indeed, when geomorphological hazards are considered, the total number of affected structures is much higher. This characteristic should be represented in any cartography to be totally truthful, although to date neither SNZCI nor PATRICOVA incorporate it [29]. Figure 3 shows the PATRICOVA flood risk assessment.…”
Section: Flood Hazards Cartography Consideredmentioning
confidence: 99%